Changes in Socio-Economic Structure Post COVID-19: A Descriptive Approach Through Literature Study - Khairunnisa Oktapela, Khairunnisa; Sri Damayanti (GoResearch - Research & Publishing House, 2024)
Before the pandemic, the socio-economic structure of many countries was in a relatively stable state with varying economic growth rates. However, COVID-19 has disrupted global supply chains, forced many businesses to close, and drastically increased unemployment. These changes have prompted the need for new adaptations in the economy and society, including in the adoption of digital technologies and changes in consumer behavior. This research is important for policymakers and industry players to design inclusive and sustainable economic recovery strategies. The qualitative research method with a literature study approach used by researchers in designing this research. And the result of this study is that the COVID-19 pandemic has had a very significant impact on various economic and social aspects, including on Micro, Small and Medium Enterprises (MSMEs).